An Analysis of Jargon Used on Facebook Found in Account “Mark Zuckerberg” - Yuni Kartika; Ainur Rohmah; Dwi Andriani (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
This study discusses An Analysis of Jargon Used on Facebook Found in account “Mark Zuckerberg”. Hopefully, this study useful for students of English Education, particularly to help them understand the jargon that is used in social media especially on Facebook. The goal of this study to find out the jargon used by